A sustainable approach for tungsten carbide synthesis using renewable biopolymers. Issue 13 (September 2017) - Islam, Monsur; Martinez-Duarte, Rodrigo
Abstract: Here we present a sustainable, environment-friendly and energy-efficient approach for synthesis of porous tungsten carbide (WC). A biopolymer-metal oxide composite featuring iota-carrageenan, chitin and tungsten trioxide (WO3 ) was used as the precursor material. The reaction mechanism for the synthesis of WC was estimated using the results from X-ray diffraction characterization (XRD). A synthesis temperature of 1300 °C and dwell time of 3 h were found to be the optimum process parameters to obtain WC>98% pure. The grain size, porosity and Brunauer–Emmett–Teller (BET) surface area of the synthesized WC were characterized using field emission scanning electron microscopy, high resolution transmission electron microscopy and nitrogen adsorption-desorption. A mesoporous WC was synthesized here with a grain size around 20 nm and BET surface area of 67.03 m 2 /g. Gel casting was used to demonstrate the manufacturing capability of the proposed precursor material. The WC obtained after heat treatment preserved the original shape albeit significant shrinkage. The WC synthesized here has potential applications in high temperature filters, catalysis, fuel cells and batteries.